2013
DOI: 10.1371/journal.pone.0057148
|View full text |Cite|
|
Sign up to set email alerts
|

Bumetanide Enhances Phenobarbital Efficacy in a Rat Model of Hypoxic Neonatal Seizures

Abstract: Neonatal seizures can be refractory to conventional anticonvulsants, and this may in part be due to a developmental increase in expression of the neuronal Na+-K+-2 Cl− cotransporter, NKCC1, and consequent paradoxical excitatory actions of GABAA receptors in the perinatal period. The most common cause of neonatal seizures is hypoxic encephalopathy, and here we show in an established model of neonatal hypoxia-induced seizures that the NKCC1 inhibitor, bumetanide, in combination with phenobarbital is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
155
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(174 citation statements)
references
References 51 publications
12
155
4
Order By: Relevance
“…Developing neocortical neurons are potentially vulnerable to the direct and indirect effects of depolarizing GABA receptors due to developmental regulation of NKCC1 as well as glutamate receptors, as previously discussed. In termequivalent rats, bumetanide has been shown to augment the neuroprotective efficacy of phenobarbital plus hypothermia following HI-and hypoxia-induced seizures without causing apoptosis (12,19). Taken together with our findings showing protection of white and gray matter following ischemic injury in preterm equivalent rats, these data indicate that NKCC1 is a modifiable molecular target in the developing brain.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Developing neocortical neurons are potentially vulnerable to the direct and indirect effects of depolarizing GABA receptors due to developmental regulation of NKCC1 as well as glutamate receptors, as previously discussed. In termequivalent rats, bumetanide has been shown to augment the neuroprotective efficacy of phenobarbital plus hypothermia following HI-and hypoxia-induced seizures without causing apoptosis (12,19). Taken together with our findings showing protection of white and gray matter following ischemic injury in preterm equivalent rats, these data indicate that NKCC1 is a modifiable molecular target in the developing brain.…”
Section: Discussionsupporting
confidence: 77%
“…While NKCC2 expression is limited to the kidney, NKCC1 is expressed more widely throughout the brain. Bumetanide effectively crosses the blood-brain barrier (12). Previously, we have shown that NKCC1 facilitates epileptiform discharges in the neonatal rodent brain, and that bumetanide attenuates epileptiform activity and enhances phenobarbital efficacy in a rat model of neonatal hypoxic seizures (10,12).…”
Section: Bumetanide Protection In Rodent Pvlmentioning
confidence: 99%
See 3 more Smart Citations